2017
DOI: 10.1111/acem.13064
|View full text |Cite
|
Sign up to set email alerts
|

Do Emergency Medicine Residency Graduates Feel Prepared to Manage Closed Fractures After Training?

Abstract: Objectives: Fractures comprise 3% of all emergency department (ED) visits. Although emergency physicians are often responsible for managing most of the initial care of these patients, many report a lack of proficiency and comfort with these skills. The primary objective was to assess how prepared recent emergency medicine (EM) residency graduates felt managing closed fractures upon completion of residency. Secondary objectives included whether residency training or independent practice contributed most to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 12 publications
1
13
0
Order By: Relevance
“… 11 However, over 40% of residency graduates across multiple programs felt only “somewhat prepared” upon graduation to handle common fracture reductions. 12 Some of this could be due to the less standardized teaching and direct feedback from orthopedic attendings, while other rotations may emphasize more observation of procedures rather than actual hands-on practice. 13 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 11 However, over 40% of residency graduates across multiple programs felt only “somewhat prepared” upon graduation to handle common fracture reductions. 12 Some of this could be due to the less standardized teaching and direct feedback from orthopedic attendings, while other rotations may emphasize more observation of procedures rather than actual hands-on practice. 13 …”
Section: Discussionmentioning
confidence: 99%
“…11 However, over 40% of residency graduates across multiple programs felt only "somewhat prepared" upon graduation to handle common fracture reductions. 12 Some of this could be due to the less standardized teaching and direct feedback from orthopedic attendings, while other rotations may emphasize more observation of procedures rather than actual hands-on practice. 13 The PGY-1 year traditionally contains the most off-service rotations, allowing PGY-1 residents to become familiar with other specialties and their practices, build interdepartmental camaraderie, and learn unique approaches to common procedures in that particular field.…”
Section: Discussionmentioning
confidence: 99%
“…However, the Accreditation Council for Graduate Medical Education does not require nor mention MSK curricula for Emergency Medicine (EM) Residency Program accreditation [13]. A recent study demonstrated 56.1% of new EM residency graduates felt "not at all prepared" or "somewhat prepared" for MSK medicine [14]. The lack of a comprehensive MSK curriculum in EM training programs highlights the need for novel strategies to provide the essential and practical foundation of MSK education.…”
Section: Impact Of Sports Medicine and Orthopedic Surgery Rotations On Musculoskeletal Knowledge In Residency Introductionmentioning
confidence: 99%
“…Another recent 2016 study evaluated 287 recent EM residency graduates from seven different residency programs to assess their level of preparedness in managing closed fractures upon completion of their residency. The study found that many graduates felt either not at all prepared (12%) or only somewhat prepared (44%) [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another study asked attending physicians to rate their subjective preparation of independent fracture reduction, which gave respondents one of four categories to choose from. These ranged from “not at all prepared,” “somewhat prepared,” “fairly well prepared,” to “very well prepared” [ 3 ], with the majority answering that they felt “somewhat prepared” [ 3 ].…”
Section: Introductionmentioning
confidence: 99%